2020
DOI: 10.1177/0883073820944051
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Architecture in Valproate-Induced Nocturnal Enuresis in Primary School and Preschool Children

Abstract: Nocturnal enuresis is one of the side effects of valproic acid treatment, and generally underdiagnosed by clinicians. Studies reported that a variable incidence of valproic acid–induced nocturnal enuresis is 2.2% to 24% with unclear explanations of the reasons behind valproic acid–induced nocturnal enuresis. A retrospective study was carried out on 260 children (aged 5-12 years) diagnosed with idiopathic epilepsy, treated with valproic acid to evaluate the nocturnal enuresis secondary to valproic acid, and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In our study, we stated that the average VPA concentration of all the 58 presented cases at the onset of enuresis was 80.76 μg/mL, which was within the recommended effective therapeutic range. Similarly, Esmael reported that, compared to the non-enuresis group, VPA concentration in the enuresis group was higher, ranging from 75.44 to 94.2 μg/mL ( 15 ). Ozan et al also reported that the VPA concentration was 76.5 ± 3.4 μg/mL when enuresis occurred, which was within the therapeutic range, while in the non-enuresis group, it was 70.8 ± 16.9 μg/mL ( 9 ).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In our study, we stated that the average VPA concentration of all the 58 presented cases at the onset of enuresis was 80.76 μg/mL, which was within the recommended effective therapeutic range. Similarly, Esmael reported that, compared to the non-enuresis group, VPA concentration in the enuresis group was higher, ranging from 75.44 to 94.2 μg/mL ( 15 ). Ozan et al also reported that the VPA concentration was 76.5 ± 3.4 μg/mL when enuresis occurred, which was within the therapeutic range, while in the non-enuresis group, it was 70.8 ± 16.9 μg/mL ( 9 ).…”
Section: Discussionmentioning
confidence: 93%
“…As an adverse effect, secondary enuresis was previously reported only in pediatric patients, and there has been no literature examining adult patients, which may be attributed to two factors. First, younger age was reported to be the only significant factor in predicting the development of enuresis ( 1 , 15 ). To our knowledge, in this study, we reported the first case of VPA-induced enuresis in an adult patient with epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reports on the effects of VPA on sleep have been conflicting, with positive, neutral and negative effects on various aspects of sleep observed across seven small studies in patients with various epilepsy conditions [38]. Further to this, VPA-associated cases of nocturnal enuresis have been reported, with studies suggesting a link to sleep architecture problems [39,40]. Overall, the effects of VPA on sleep need to be addressed in larger dedicated studies in DEEs, although the prevalent use of this ASM suggests that problems are likely to be minimal.…”
Section: Valproate (Vpa)mentioning
confidence: 99%